2020
DOI: 10.1177/0146167220927195
|View full text |Cite
|
Sign up to set email alerts
|

Rule Following Mitigates Collaborative Cheating and Facilitates the Spreading of Honesty Within Groups

Abstract: Compared with working alone, interacting in groups can increase dishonesty and give rise to collaborative cheating—the joint violation of honesty. At the same time, collaborative cheating emerges some but not all of the time, even when dishonesty is not sanctioned and economically rational. Here, we address this conundrum. We show that people differ in their extent to follow arbitrary and costly rules and observe that “rule-followers” behave more honestly than “rule-violators.” Because rule-followers also resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…Similarly, manipulations implemented to reduce/increase collaborative dishonesty influence groups’ reports. For example, Gross and De Dreu (2021) preclassified participants as rule followers or rule violators and then assigned them to dyads in which two rule followers (violators) interacted with one another. The standardized group report was 15.68% when two rule followers interacted with one another and 40.65% when two rule violators interacted with one another.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, manipulations implemented to reduce/increase collaborative dishonesty influence groups’ reports. For example, Gross and De Dreu (2021) preclassified participants as rule followers or rule violators and then assigned them to dyads in which two rule followers (violators) interacted with one another. The standardized group report was 15.68% when two rule followers interacted with one another and 40.65% when two rule violators interacted with one another.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies show that social information about other people’s ethical rule violations increases people’s own propensity to break ethical rules (Ferrali, 2020; Gächter & Schulz, 2016; Gino et al, 2009; Keizer et al, 2008; Köbis et al, 2015; Köbis, Troost, et al, 2019; Kocher et al, 2018; O’Fallon & Butterfield, 2012; but see Dimant et al, 2020). Recent work on collaborative dishonesty indeed finds that one group member’s lies increase the likelihood that the partner will also lie (Gross et al, 2018), and that having rule followers in a group mitigates the spread of collaborative dishonesty (Gross & De Dreu, 2021).…”
Section: Theoretical Perspectives On Collaborative Dishonestymentioning
confidence: 99%
“…Not providing a specific frame or trigger ethical considerations to follow the rule was important for us, as it otherwise could lead to a selection and signal of interindividual differences over and beyond simply following a costly rule (for example, underlying moral convictions), which is not the aim here. The behavioral rule following task has been shown to correlate with personality traits like need for structure (Gross & De Dreu, 2017), cooperation in social dilemma situations, and respecting norms like trust, prosociality, and honesty (Gross & De Dreu, 2020;Kimbrough & Vostroknutov, 2016;Kimbrough, Miller, & Vostroknutov, 2014). Resonating with the idea that rules create a conflict between restricting behavior and maximizing own benefits (Pfister, Wirth, Schwarz, Steinhauser, & Kunde, 2016;Pfister, Wirth, Weller, Foerster, & Schwarz, 2018), a recent brain stimulation study also showed that rule following is causally linked to the right lateral prefrontal cortex, a brain region that has been associated with value-based cost-benefit decisions (Gross, Emmerling, Vostroknutov, & Sack, 2018a).…”
Section: Methodsmentioning
confidence: 99%
“…If individuals prefer more money to less and if there is a normative expectation that participants in a study ought to comply with the requests of a researcher, then the extent of rule-following in the task proxies for an individual’s propensity to follow injunctive norms. Indeed, behaviour in the RF task has been shown to predict norm-consistent behavior across a variety of tasks (see Kimbrough and Vostroknutov 2015 37 , 2016 24 , 2018 25 ; Ridinger 2018 38 ; Gross and DeDreu 2021 39 ).…”
Section: Methodsmentioning
confidence: 99%